Microgenetic Analysis of Moral Development: Theoretical and Methodological Issues - Barrios, Alia (2012)
New ideas and methodologies need to be developed to advance our knowledge in the understanding of moral development. The intertwined nature of human activities, communication processes, and the numerous aspects of morality pose a challenge to researchers to construct a methodology that takes into account cognition, affect, sociocultural processes and characteristics, as well as the active role of individuals in their own development. In this paper we aim at suggesting fresh theoretical ideas and a micro genetic methodology to study moral development, particularly within educational contexts.